Recommendations of the Council of Europe as a Guide for the Development of Criminal Executive Law of Ukraine - Haltsova, Olena V. (2022)
The recommendations of the Council of Europe are based on the rich European experience of execution of punishments in the field of criminal-executive law, as well as the generalisation of the positive achievements of the national legislation of the most developed countries in this respect. In its recommendations, the Committee of Ministers of the Council of Europe calls on States to improve the legislation and practices of their respective agencies with a view to increasing the application of alternative sanctions and measures, which should ultimately reduce the number of people held in prisons. The aim of the article is to determine the degree of consideration of the recommendations of the Council of Europe on changes in certain norms of legislation in the field of criminal executive law. The main approach is the methodology of comparative analysis of the domestic penitentiary system and its legal framework in the world and the European Union, as well as the previous system in Ukraine, which has changed in accordance with the recommendations of the Council of Europe. Based on the results of the analysis, the priority areas for implementation of the recommendations provided by the Council of Europe concerning the observance of rights in the penitentiary system have been identified. In the future, it is of interest to compare the legislative support of the penitentiary system in the light of the further implementation of the recommendations of the Council of Europe in the context of the implementation of relevant norms in the domestic legislation and their realisation in practice